Reward or Punishment, Which is Better to Use in Elementary Schools? - Safitri, Mazda Leva Okta; Hermawan, Rudi; Sari, Yeasy Agustina (Bulletin of Science Education, 2023)
The application of punishment and the giving of reward are important parts of education. However, sometimes the implementation of punishment and the giving of reward is still not appropriate. This research is a literacy study. This study aims to provide a reference on various forms of reward and punishment used in elementary schools. The method used is collecting several references and drawing the best conclusions from the source. The stages used in this research are collecting sources, describing the content, and drawing conclusions. Various forms of punishment and rewards are used according to the level of moral development of the child. Although it is said that rewards are more effective than punishment, the use of punishment still needs to be done because rewards cannot replace the role of punishment as a means of controlling behavior. The combination of reward and punishment is the best educational tool. Keywords: Reward in Learning, Punishment in Learning, Elementary Schools Learning